PENGARUH TINGKAT PENDIDIKAN, MASA KERJA, PELATIHAN DAN JABATAN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH KABUPATEN MINAHASA SELATAN - Wungow, Jhon Fiesgrald; Lambey, Linda; Pontoh, Winston (Universitas Sam Ratulangi, 2016)
This study is aimed to examine the effect of educational level, working period, training and government officers of the quality of government financial reports South Minahasa regency simultaneously and partially. The population was taken employees who work as treasurers and chiefs financial sub-section of the local work units and in accounting and treasury areas in the Office of Financial Management, Revenue and Asset South Minahasa regency. The research sample was 100 respondents and only 95 respondents who participated by answering questionnaires. The variables in this study are independent variable consist of level of education (X1), working period (X2), training (X3) and government officers (X4) on the other hand, dependent variable is the quality of local financial statement (Y). Data were analyzed using multiple linear regression analysis (multiple regression). The results showed that the level of education, working period, training and official simultaneously have a significant impact on the quality of local financial statement. The value of the coefficient of determination shows that the level of education, working period, training and government officers together contribute to the quality of local financial statements in the amount of 40.1%, while the remaining of 59.9% is influenced by other factors beyond the research model. Partial test results showed that only training and government officers have an impact on the quality of local financial statement. The level of education and working period do not have any influence on the quality of government financial reports South Minahasa regency. Keywords: quality of local financial statement, level of education, working period, training, government officers.